2021
DOI: 10.1111/jvim.16106
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of ventricular septal defects in a non‐racehorse equine population (2008‐2019)

Abstract: Background: Ventricular septal defects (VSDs) are the most common congenital cardiac defect in horses.Objectives: To identify prevalence, age, breed, and sex distribution of VSD and to describe associated clinical and ultrasonographic findings.Animals: Hospital-based population of 21 136 horses presented to the equine internal medicine department.Methods: Medical records over a 12-year period were reviewed for VSD confirmed by ultrasonography. Age, breed, sex, sport discipline, murmur, clinical signs, outcome,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 23 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…In equids, several isolated and complex congenital cardiac defects have been reported. These are usually diagnosed after a cardiac murmur has been detected [ 13 , 17 ]. However, loud cardiac murmurs in foals shortly after birth in the absence of signs of cardiovascular compromise can be physiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…In equids, several isolated and complex congenital cardiac defects have been reported. These are usually diagnosed after a cardiac murmur has been detected [ 13 , 17 ]. However, loud cardiac murmurs in foals shortly after birth in the absence of signs of cardiovascular compromise can be physiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…1,25 VSDs can occur either as isolated defects or as a component of complex cases, with the prevalence of concomitant defects within VSD cases ranging from 22% to as high as 60%; however, this may be an overrepresentation as the reported study populations are either from hospitals or necropsies that are more likely to include defects of greater severity. 7,8,26 Nevertheless, the presence of other defects should be excluded in diagnosis, with additional defects often producing more severe clinical signs and a worse prognosis than isolated VSD cases. 2,4,7,10,17 A VSD occurs in cases of inadequate convergence and fusion of the primitive ventricular septum, the atrioventricular cushions and the conal ridges.…”
Section: Ventricular Septal Defectmentioning
confidence: 99%
“…1 VSDs in horses can be classified as three main phenotypes based on their location: perimembranous, infundibular or muscular. 10,25,26 The most common type is the perimembranous or paramembranous VSD, located in the fibrous area of the membranous septum below the septal leaflet of the tricuspid valve and the junction of the right and non-coronary cusps of the aortic valve. 10,25,26 Infundibular, subarterial, doubly committed or subpulmonic VSDs are located in the fibrous continuity below the pulmonary and aortic valve leaflets.…”
Section: Ventricular Septal Defectmentioning
confidence: 99%
See 1 more Smart Citation
“…VSD was the most common single and combined cardiac malformation in our study, as reported in other domestic species. 3,7 VSDs typically caused right-sided dilation; identification of the defect is reasonably straightforward based on the identification of a hole that connects the 2 ventricles. In our case series, a right-to-left shunt caused by significant pulmonary hypertension was not identified in any of the patients.…”
mentioning
confidence: 99%